Characteristics of recurrent acute urinary retention in BPH patients in the United States: Retrospective analysis of US‐based insurance claims database. Issue 7 (9th March 2023) - Lee, Sinyeong; Yoo, Koo Han; Kim, Taek Sang; Cho, Hyuk Jin; Kim, Wansuk; Oh, Jin Kyu; Li, Shufeng; Kim, Sang Youn; Wei, Wuran; Huang, Jianlin; van Uem, Stefanie; Del Giudice, Francesco; et al.
Abstract: Purpose: The objective of this study is to analyze characteristics of recurrent acute urinary retention (AUR) in patients with benign prostatic hyperplasia (BPH), utilizing a population based data set. Also, we sought to report on how AUR was treated, specifically regarding the need and length of catheterization and types of procedures utilized for mitigation. Materials & Methods: A retrospective observational cohort study was performed using Optum's deidentified Clinformatics® Data Mart Database. We compared two groups, BPH patients with AUR ( n = 180, 737) and BPH patients without AUR ( n = 1, 139, 760) from January 1, 2003 to December 31, 2017. Also, we analyzed the factors affecting the development of multiple episodes of AUR through age‐adjusted multivariate analysis. Results: In contrast to the 47.7% of patients who had a single AUR episode, 33.5% of AUR patients developed 3 or more subsequent episodes of retention. For age matched patients, the risks of additional episodes of retention increase significantly with older age, Caucasian race, diabetes, neurologic conditions, or low income. Overall, the rate of BPH surgery in AUR patients over the study period decreased and the most common procedure was transurethral resection of the prostate. Conclusions: Risk factors for multiple episodes of AUR included age (60 and older), Caucasian race, lower income socioeconomic status, diabetes, and neurological disorders. Patients with a high probability of developing recurrent episodes of AUR are recommended to receive preemptive BPH medication before such AUR occurrences. Also, more expeditious surgical treatment should be considered rather than temporary catheterization when AUR occurs.